Advances in parasitology. - Rollinson, D. (Advances in parasitology ;, 2013)
First published in 1963, Advances in Parasitology contains comprehensive and up-to-date reviews in all areas of interest in contemporary parasitology. Advances in Parasitology includes medical studies on parasites of major influence, such as Plasmodium falciparum and trypanosomes. The series also contains reviews of more traditional areas, such as zoology, taxonomy, and life history, which shape current thinking and applications. Eclectic volumes are supplemented by thematic volumes on various topics, including control of human parasitic diseases and global mapping of infectious diseases.